NILAI-NILAI KEARIFAN LOKAL BERWAWASAN PELESTARIAN LINGKUNGAN DI KAMUNG CIREUNDEU SEBAGAI SUMBER PEMBELAJARAN IPS : Studi Deskriptif Kualitatif di Kampung Cireundeu Kecamatan Cimahi Selatan Kota Cimahi - Fardan Faliq, - (2019)
This research aims to expose the utilization of local wisdom values with an insight into environmental preservation in Kampung Cireundeu as an educational source of IPS. As for the background of this research is the observation of researchers during the teaching practice in one of the first secondary schools in the city of Bandung, which results in a lack of awareness of learners in maintaining hygiene Environment. It is seen from still many learners who throw garbage out of place, resulting in a lot of garbage that is in the school environment. The purpose of the implementation of this research is to know how the traditions and cultural values contained therein, knowing the efforts of the CIREUNDEU community in maintaining environmental sustainability through the values of traditions, And know the values of local wisdom of the Cireundeu community that can be used as a learning source IPS. This research is a qualitative descriptive study carried out in Kampung Adat Cireundeu District of South Cimahi, Cimahi. The technology used for data collection is observation techniques, interviews, and documentation. The results of this research show that the traditions and values of the culture of Cireundeu society are still kept in its sustainability. The use of good Sundanese language, traditional ceremonies, art is still continued to be carried out today. Cireundeu community effort in maintaining environmental sustainability through the values of tradition by dividing the indigenous territories into three parts of the region namely Leuweung larangan, Leuweung tutupan, and Leuweung Baladahan. And do environmental-friendly planting patterns. Local wisdom values of the Cireundeu community can be used as a source of learning IPS because it can arouse the awareness of students to maintain the environment for the fulfillment of obligations as citizens who are in the law.